Magnetohydrodynamic boundary layer flow in a nanofluid with various stream conditions - Mohamad, Radiah (2017)
Magnetohydrodynamic (MI-ID) nanofluids boundary layer flow, is one of the fields of study that has caught the attention of many researchers due to the extensive applications of this flow in extrusion of plastics, the cooling of reactors, textile industry, polymer technology, metallurgy, geothermal engineering and liquid metals and plasma flows. This thesis investigates the convective heat transfer in magnetohydrodynamic boundary layer flow of nanofluids over various geometric surfaces (flat, vertical or wedge) subjected to different boundary conditions. Two models were used in this study: Tiwari-Das model that takes into account the effect of the volume fraction of nanoparticles and Buongiomo model that combines the effects of Brownian motion and termoforesis. Five problems are considered in this study taking into account the effect of various parameters such as the effect of the magnetic field, the volume fraction of nanoparticles, Brownian motion, thermophoresis, chemical reactions, thermal stratification and the presence of micro organisms and particles of carbon nanotubes (CNTs). In all cases, the mathematical models which resemble the physical flow of the problems are developed. The governing partial differential equations are reduced to a system of ordinary differential equations by using one of the following transformations: similarity transformation, local similarity transformation or local non-similarity transformation. These ordinary differential equations are then solved numerically using the shooting method for different boundary conditions. Numerical solutions for velocity, temperature and concentration profiles as well as the skin friction coefficient or local Nusselt number are obtained and presented either graphically or in tabular forms and the main features of the problems are discussed and analyzed. It is observed that the skin friction coefficient and the local Nusselt number which represents the heat transfer rate at the surface are significantly influenced by all the parameters studied. Using the Tiwari-Das model, the results indicate that increasing the volume fraction of nanoparticles increases the skin friction coefficient and the local Nusselt number. The results also showed that carbon nanotubes (CNTs) are the best particles to be dispersed in common based fluid due to its unique thermal properties and structure. Although producing the governing equations for the Tiwari-Das model is simpler than that of Buongiorno model, Tiwari-Das model ignores the velocity slip effect of nanoparticles which is important in explaining the existence of nanoparticles in the base fluid. Instead in Buongiorno model, these velocity slips are rep.resented by the Brownian motion and thermophoresis parameters. However, results showed that both of these effects only affect the temperature and concentration profiles but not the velocity flow profiles.